2007
DOI: 10.1159/000109877
|View full text |Cite
|
Sign up to set email alerts
|

Corticotropin-Releasing Hormone and Pro-Opiomelanocortin Gene Expression in Female Monkeys with Differences in Sensitivity to Stress

Abstract: Background/Aims: The expressions of corticotropin-releasing hormone (CRH) and pro-opiomelanocortin (POMC) were assessed in brain tissue collected from nonstressed female cynomolgus monkeys previously categorized as highly stress resilient (HSR), medium stress resilient (MSR), or stress sensitive (SS) with respect to stress-induced anovulation. Methods: In situ hybridization and quantitative image analysis was used to measure mRNAs coding for CRH in the hypothalamic paraventricular nucleus (PVN) and thalamic ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 91 publications
0
26
2
Order By: Relevance
“…The CRF innervation of the dorsal raphe is believed to originate in the caudal portion of the PVN and in the amygdala, where we had previously observed an increase in CRF in SS individuals relative to SR individuals [13]. This difference was reflected in the CRF fiber density in the dorsal raphe of the Pb-treated animals.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…The CRF innervation of the dorsal raphe is believed to originate in the caudal portion of the PVN and in the amygdala, where we had previously observed an increase in CRF in SS individuals relative to SR individuals [13]. This difference was reflected in the CRF fiber density in the dorsal raphe of the Pb-treated animals.…”
Section: Discussionmentioning
confidence: 84%
“…More recently, gynecologists have recognized that individual differences in stress sensitivity play a role in the pathology of infertility [4,40]. We have previously shown that monkeys who are sensitive to stress-induced amenorrhea exhibit significantly more CRF mRNA and CRF protein in the caudal region of the PVN, significantly more CRF mRNA in the thalamus and a significantly higher CRF fiber density in the central nucleus of the amygdala relative to stress-resilient animals under nonstressed basal conditions [13]. In contrast, rodent strains with different sensitivities to stress exhibit no difference in hypothalamic CRF expression [41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding does not support the hypothesis that SS monkeys have elevated chronic basal activity of the HPA axis. We had explored this hypothesis in part because we had reported previously that both MSR and SS monkeys have increased CRH gene expression in the caudal paraventricular nucleus (PVN), amygdala, and thalamus compared with HSR monkeys (18). Both glucocorticoids and CRH itself have been shown to be capable of suppressing reproductive axis activity in some circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies show that female rhesus monkeys that are most reactive to stress are characterized by diminished serotonergic (5HT) activity, evidenced by reduced response to the 5HT transporter (5HTT) inhibitor-5HT releaser fenfluramine [13], reduced expression for the genes encoding the 5HTT (SLC6A4) and monoamine oxidase A (MAOA) in the dorsal raphe [14], and reduced 5HT receptor expression in the paraventricular nucleus of hypothalamus and infundibulum [15], and greater corticotropin-releasing hormone (CRH) expression in limbic-hypothalamic regions [16]. Diminished 5HT function is associated with traitlike disinhibition of behavior in response to social adversity, including increased impulsivity and aggression as well as poor regulation of affect [17,18].…”
Section: Introductionmentioning
confidence: 99%